The legacy of mRNA engineering: A lineup of pioneers for the Nobel Prize - Miroslaw Janowski; Anna Andrzejewska (Molecular Therapy: Nucleic Acids, 2022)
mRNA is like Hermes, delivering the genetic code to cellular construction sites, so it has long been of interest, but only to a small group of scientists, and only demonstrating its remarkable efficacy in coronavirus disease 2019 (COVID-19) vaccines allowed it to go out into the open. Therefore, now is the right timing to delve into the stepping stones that underpin this success and pay tribute to the underlying scientists. From this perspective, advances in mRNA engineering have proven crucial to the rapidly growing role of this molecule in healthcare. Development of consecutive generations of cap analogs, including anti-reverse cap analogs (ARCAs), has significantly boosted translation efficacy and maintained an enthusiasm for mRNA research. Nucleotide modification to protect mRNA molecules from the host’s immune system, followed by finding appropriate purification and packaging methods, were other links in the chain enabling medical breakthroughs. Currently, vaccines are the central area of mRNA research, but it will reach far beyond COVID-19. Supplementation of missing or abnormal proteins is another large field of mRNA research. Ex vivo cell engineering and genome editing have been expanding recently. Thus, it is time to recognize mRNA pioneers while building upon their legacy.